Human stem cells express pannexins - Hainz, Nadine (BMC Res Notes, 2018)
OBJECTIVE: Pannexins are channel proteins important for the release of calcium and adenosine triphosphate, which are among other functions involved in early development. Here, the expression of pannexins was investigated in induced pluripotent stem cells derived from human cord blood endothelial cells (hCBiPS2), in hematopoietic stem cell-derived induced pluripotent stem cells (HSC_F1285_T-iPS2) and in human embryonic stem cells (HES-3). The expression of pannexin (Panx) 1–3 mRNAs was analyzed in all three undifferentiated stem cell lines. Stem cells then underwent undirected differentiation into embryoid bodies and were analyzed regarding expression of germ layer-specific genes. RESULTS: Panx1, Panx2, and Panx3 mRNAs were expressed in all undifferentiated stem cell lines investigated. In comparison, Panx1 showed the highest expression among all pannexins. The undirected differentiation resulted in a mixed germ layer genotype in all three stem cell lines. Whereas the expression of Panx1 was not affected by differentiation, the expression of Panx2 was slightly increased in differentiated hCBiPS2 cells, HSC_F1285_T-iPS2 as well as HES3 cells as compared to their undifferentiated counterparts. A slight increase of Panx3 expression was observed in differentiated hCBiPS2 cells only. In conclusion, pluripotent stem cells express all three pannexin genes. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13104-018-3125-z) contains supplementary material, which is available to authorized users.